Assessment of the impact of orthodontic-surgical treatment on the quality of life of patients with mandibular prognathism - Ilić, Jana; Čutović, Tatjana; Kozomara, Ružica; Radojičić, Julija; Adamović, Tijana; Lovrić, Jovana (Vojnosanitetski pregled, 2023)
Background/Aim. Mandibular prognathism, as one of the more severe forms of dentofacial deformities, impairs the oral functions and appearance of the patient’s face and represents a psychosocial handicap with a negative impact on the quality of life (QoL). The aim of the study was to assess the impact of orthodontic-surgical (OS) treatment on the QoL of patients with mandibular prognathism. Methods. The study involved 40 patients (19 men and 21 women, with a mean age of 24.1 ± 4.1 years) who underwent the OS treatment for mandibular prognathism. All patients completed two questionnaires – the Oral Health Impact Profile (OHIP-14) and the Orthognathic Quality of Life Questionnaire (OQLQ), before the start of treatment and 12 months after the completion of treatment. Results. The results of both questionnaires showed an improvement in the QoL compared to the condition before the treatment. According to the OQLQ questionnaire, there was a postoperative improvement in the QoL (score 24.8 ± 12.9) compared to the preoperative period (score 51.3 ± 15.2). According to the results of the OHIP-14 questionnaire, there was a postoperative improvement in the QoL (score 11.3 ± 2.9) compared to the preoperative period (score 20.8 ± 6.9). The improvement of the QoL, 12 months after the treatment, occurred in all life segments, measured by both questionnaires. Conclusion. OS treatment of mandibular prognathism improves all oral functions, including the appearance of the patient’s face, thus improving the QoL.